High efficacy of azacitidine combined with homoharringtonine, idarubicin, and cytarabine in newly diagnosed patients with AML: A single arm, phase 2 trial - Li, Jun; Huang, Yanqing; Hou, Yue; Gu, Yan; Song, Chunhua; Ge, Zheng (Frontiers in Oncology, 2022)
This study aims to evaluate the efficacy and safety of the novel combination of Aza and HIA as the frontline induction therapy in newly diagnosed AML patients eligible for intensive chemotherapy (IC) (registered on ClinicalTrials.gov, number NCT04248595). Aza (75mg/m2/d on days1-5 subcutaneous) is administered in combination with HIA [HHT 2mg/m2/d on days 4-8 intravenous over 3 hours, idarubicin 6mg/m2/d on days 4-6 intravenous, and cytarabine 100mg/m2/d on days 4-10 intravenous]. The primary endpoint was complete remission (CR) or CR with incomplete blood count recovery (CRi). Secondary endpoints were overall survival (OS), relapse-free survival (RFS), and adverse events (AEs). A total of 20 AML patients (aged 18-70 years) were enrolled between Jan 2020 and Sep 2022. 95% (19/20) of patients achieved CR/CRi, and 89.5% (17/19) had undetectable MRD, in which 94.7% (18/19) reached CR/CRi, and 88.9% (16/18) obtained MRD negative after the 1st cycle of induction therapy. Median OS and RFS were both not reached during the follow-up. The estimated 2-year OS and RFS were 87.5% (95%CI, 58.6% to 96.7%) and 87.1% (95%CI, 57.3% to 96.6%), respectively. No patient discontinued the treatment for AEs. This study provides preliminary evidence for this novel combination therapy as the first-line induction therapy for young or older AML patients fit for IC.